Recycling as play: encouraging recycling through a participatory design process with children - Santoro, Amanda (Kansas State University, 2016)
Recycling in many cities faces dilemmas with accessibility and education, especially within the public realm, which leads to a lack of participation in this sustainable activity. The City of Kansas City, Missouri does not currently provide recycling solutions for multi-family and commercial businesses and has minimal to non-existent recycling infrastructure within its downtown’s public realm. Envisioning a new recycling system for a city requires many entities to come together in the design process. However, the city, landscape architects, and other designers frequently overlook incorporating children into the participatory community design process, even though children have knowledge, experiences, and ideas to offer (Speak, 2000). Incorporating many avenues of community input can benefit the design outcomes, and children should be included in the participatory design process when it engages their built environment. The Kansas City Design Center (KCDC) produced a vision plan and conceptual site designs for downtown Kansas City’s recycling system. Community input was part of the KCDC studio project’s design process by utilizing a series of advisory council meetings, professional reviews, and open houses. This report integrated another form of community involvement into the project by working with children on designing urban space and playful infrastructure focused on encouraging participation in recycling. A series of design charrettes were conducted with 5th grade students from Kansas City’s urban charter school Crossroads Academy due to the school’s focus on immersion in the urban environment. The students’ design charrette ideas added a new perspective to how urban space and recycling infrastructure could encourage participation. These ideas and perspectives were shared with classmates and utilized to further design development in the recycling project's streetscape "Links" strategy. As the project developed, the researcher observed how the children's ideas impacted the "Links" strategy design coming through in playful ground plane designs, interactive elements, concepts of place-making, and considerations for a variety of users. The participatory process with the children was most influential on those involved directly with the children's process. This allowed the children's ideas to become inherent base knowledge when designing. Engaging youth’s imaginative minds in the design process for urban space and recycling infrastructure sparked new playful perspectives on how to encourage participation and led to meaningful recycling design outcomes within the public realm.
Keywords: Children; Participatory process; Landscape architecture; Recycling